The Building up of Peace: the Project of the Abbé of Saint-Pierre - Bello, Eduardo (Res Publica. Revista de Historia de las Ideas Políticas, 2015)
Firstly, the author endorses the idea that the project of perpetual peace conceived by the abbé of Saint-Pierre has contributed to a modification of the understanding of war and peace in our culture. Secondly, the paper defends that this project is also decisive in the history of international right insofar as it pointed in the direction of a supranational juridical approach to the resolution of conflicts. Finally, it is still meaningful for improving the federal solution to Europe’s problems.
Keywords: European Confederation; Perpetual Peace; Civil War; International war; Interstate Equilibrium.